2014
DOI: 10.1111/aab.12135
|View full text |Cite
|
Sign up to set email alerts
|

Induced systemic resistance and growth promotion in tomato by an indole‐3‐acetic acid‐producing strain of Paenibacillus polymyxa

Abstract: Paenibacillus polymyxa strain CF05, a plant-growth-promoting rhizobacterium (PGPR) showed inhibitory effect on Fusarium oxysporum f. sp. lycopersici in vitro, causal agent of Fusarium-wilt of tomato. In the greenhouse experiments, tomatoes inoculated with strain CF05 promoted the significant growth. Meanwhile, strain CF05 suppressed the Fusarium-wilt with 78.24% in control efficiency, which was similar to the carbendazim treatment. The bacterial culture supernatant was found to have the presence of indole-3-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…In addition, inoculation with P. polymyxa led to accumulation of phenolic compounds, which, together with induced defence enzymes, could defend C. cathayensis trunks against infection by the canker‐causing pathogen. Similar patterns of induction by bacteria have been reported in other plants, including tomato roots (Mei et al., ), Arabidopsis thaliana (Timmusk & Wagner, ) and cucumber (Benhamou, Gagne, Quere, & Dehbi, ; Chen et al., ). This study, however, is the first report in which antagonistic bacteria induced plant defences on the tree trunk.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, inoculation with P. polymyxa led to accumulation of phenolic compounds, which, together with induced defence enzymes, could defend C. cathayensis trunks against infection by the canker‐causing pathogen. Similar patterns of induction by bacteria have been reported in other plants, including tomato roots (Mei et al., ), Arabidopsis thaliana (Timmusk & Wagner, ) and cucumber (Benhamou, Gagne, Quere, & Dehbi, ; Chen et al., ). This study, however, is the first report in which antagonistic bacteria induced plant defences on the tree trunk.…”
Section: Discussionsupporting
confidence: 76%
“…Paenibacillus polymyxa strain CF05 was isolated from the interior of an ancient Cryptomeria fortunei (syn. Cryptomeria japonica) tree growing on Tianmu Mountain, Zhejiang, China, and stored at −80°C (Mei, Liang, Zhang, Wang, & Guo, 2014). The pathogenic fungus B. dothidea CK16 was isolated from typical symptoms of Chinese hickory trunk canker.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was used to measure Fe content by inductively coupled plasma-atomic emission spectroscopy according to the method reported by Lei et al (2014). Additionally, the production of indole acetic acid (IAA) by bacteria in the culture medium was detected according to the method of Mei et al (2014). The content of IAA in plants was examined by gas chromatography as reported by Ljung et al (2005).…”
Section: Determination Of Fe and Iaa Contentmentioning
confidence: 99%
“…Many parameters such as age, temperature, pH, and in particular nutrient composition of the media affect metabolite production by an organism and can result in different bioactivity outcomes to an in vitro study. On the other hand, antibiosis is only one of the mechanisms involved in the biocontrol activity of Paenibacillus spp.. Competition, root colonization (Haggag and Timmusk, 2008), and induced systemic resistance (Mei et al, 2014) have also been reported as possible modes of action of Paenibacillus spp., and these cannot be determined using a dual culture assay. Hence, the high biocontrol activity that P16 exhibited against black rot disease in cabbage, despite the lack of bioactivity in vitro, appears to be due to mechanisms other than antibiosis.…”
Section: Discussionmentioning
confidence: 99%